Physical Fitness Profile of Wheelchair-Bound Soldier: A Preliminary Study - Endang Ernandini; Trevino A. Pakasi (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTIntroduction: The Regulation of the Ministry of Defense No. 106 of 2016 regulates the process ofwhether a disabled soldier should retire or continue their career. Some soldiers can continue afterundergoing a rehabilitation program and fitness test called Uji Kesamaptaan. Unfortunately, the currentscoring system in Uji Kesamaptaan only fits for normal soldiers. The purpose of this study was todescribe the profile of normal and disabled soldiers who underwent physical fitness tests. The equalityvalue “Kesamaptaan table” with the running test can be used to assess the ability for disabilities by usinga wheelchair test?Methods: This preliminary study used a cross-sectional method and involved 46 soldiers who weredivided into two groups, disabled (n=16) and normal (n=30). All participants underwent a 12-minuterun or wheel test in a 400-meter track, to record the distance covered according to their ability. VO2Maxassessed using the Cardio-Pulmonary Exercise Test (CPET). Results were analyze using SPSS program;Independent T-test.Results: No significant difference was observed in the characteristics (age, body weight, height, andmass index) between the two groups. The VO2Max difference between normal soldiers and disabledsoldiers was highly significant. The highest score among disabled and normal soldiers was 38 L/min/kgBW and 64 L/min/kg BW, respectively. Normal soldiers covered 465m farther in a 12-minute run test.Conclusion: Kesamaptaan, the current scoring system for soldiers, can be considered unfair for thedisabled soldiers. The scoring system only includes for 12-minutes running test. Differences in theinvolvement of muscles and muscle type, affecting energy use and oxygen consumption between the12-minute run test and wheelchair pedal test. Therefore, value conversion is required for disabledsoldiers.Keywords: disabled persons, exercise test, physical fitness, VO2Max